2015
DOI: 10.1016/j.jcf.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in CF and non-CF homes is found predominantly in drains

Abstract: These findings implicate drains as important potential sources of P. aeruginosa infection. They suggest that maximizing P. aeruginosa control efforts for drains would reduce exposure with minimal extra burden to CF patients and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
2
28
3
Order By: Relevance
“…but also by several other known CF opportunistic pathogens (17)(18)(19)(20), including Stenotrophomonas maltophilia, Bordetella, Ochrobactrum, and Agrobacterium/ Rhizobium. As shown in previous studies, wastewater drains are the primary habitat of P. aeruginosa (10)(11)(12)(13); we confirm that siphons and other similar draining systems host a large number of opportunistic pathogens. These devices are more and more frequently described as reservoirs for pathogens and multidrug-resistant bacteria in both hospitals and domestic environments (21)(22)(23).…”
supporting
confidence: 89%
“…but also by several other known CF opportunistic pathogens (17)(18)(19)(20), including Stenotrophomonas maltophilia, Bordetella, Ochrobactrum, and Agrobacterium/ Rhizobium. As shown in previous studies, wastewater drains are the primary habitat of P. aeruginosa (10)(11)(12)(13); we confirm that siphons and other similar draining systems host a large number of opportunistic pathogens. These devices are more and more frequently described as reservoirs for pathogens and multidrug-resistant bacteria in both hospitals and domestic environments (21)(22)(23).…”
supporting
confidence: 89%
“…Recovery of P . aeruginosa from this sampling effort is described elsewhere [ 29 ], and, consistent with other studies of human households, indicated that this species differs from other Pseudomonas in being almost a drain specialist in a household context [ 14 , 29 32 ]. We explored a broad range of types of environments both inside and outside the home, in a longitudinal study including 15 households sampled up to 8 times each, over a 4.5-year period.…”
Section: Introductionsupporting
confidence: 76%
“…They may also contaminate similar environments in the home. PA has been found in the home environment, commonly in sinks and drains [8,9]. However, in only 9 out of 50 patients with acute PA infection was an identical strain isolated in both the patient and their home environment [9].…”
Section: Out Of Hospital Acquisition Through Environmental Reservoirsmentioning
confidence: 99%